Review of various social issues in the novel "The Ministry of Utmost Happiness" by Arundhati Roy - Gill, Navjot (Innovative Research Thoughts, 2017)
Since the Indian subcontinent was liberated from colonial rule, post-colonial theory has been one of the most popular academic topics to study. The term subaltern is a product of the post-colonial condition that has spawned a plethora of literature. Subaltern's definition and features have changed greatly as a result of socioeconomic advancement. Arundhati Roy, a self-aware author, has used her second novel, The Ministry of Utmost Happiness, to hide current social and political issues vital to the study of the "subaltern," particularly in the South Asian setting.. The book is dedicated to The Un consoled, a group of Indians who have been uprooted and disenfranchised by the country's fast change. The transgender problem was brought to light via the novel's protagonist or central character. Many other social and political issues, such as discrimination against women and people of color, caste, capitalism, and many more, were also addressed. Activist Arundhati Roy has published several works about capitalism, globalization, and democracy over her career. Consequently, The Ministry of Utmost Happiness is unquestionably and intuitively an explosion of the author's observation of the "The New Subaltern" who are the victims of social and political unfairness in society. "The New Subaltern" shown in this article is examined via the lens of Roy's characters, who are placed in a post-colonial context. This article seeks to chronicle the evolution of subaltern studies in South Asia, which is always evolving. "Subaltern Studies" in broad post-colonial literary studies are given a boost by this piece, which shows Roy's vision of the new subaltern in The Ministry of Utmost Happiness. This also examines the novel's characters, language, and socio-political setting offered by the author.